Produção e caracterização de fermentado alcoólico e vinagre de físalis e pitaia como estratégia de aproveitamento tecnológico - Fernandes, Annayara Celestina Ferreira (2016)
The production of exotic fruits has attracted the attention of consumers, traders and, consequently, producers on familiar, medium and large scale. The association of these fruits to the nutraceutical properties, such as high levels of antioxidants and anti-cancer substances, increases acceptance by the consumer, who is seeking a nutritionally balanced and healthy diet. The sale of fruits processed into industrial products, such as the alcoholic fermentation and vinegar can be a good alternative for small producers and a possible spread of these plants in Brazil. The objectives of this study were to develop alcoholic fermentation and acetic (vinegar) of físalis and pitaya, the determination of the antioxidant potential of vinegars and evaluation of acceptance of the new product and the antimicrobial potential. Initially was produced alcoholic fermentation of the fruits, using the yeast Saccharomyces cerevisiae CCMA 0200 and the fermentations were monitored daily, measuring the number of viable cells in suspension, pH, Brix and carrying out analyzes chromatographic compounds of interest . The ethanol concentration at the end of the alcoholic fermentation process, were 80.95 g.L-1 (10.2 ºGL) in the físalis must and 84.71 g.L-1 (10.6 ºGL) in the pitaya must. In sequence, the acetic fermentation were prepared in bioreactor bench, using mixed culture of acetic bacteria: Acetobacter aceti (CCT 0190), Acetobacter pasteurianus (CCMA 0239) and Gluconobacter oxydans (CCMA 0350). The yield of acetic acid was 75% and productivity of 0.30 gl-1.h-1 for físalis vinegar and 72% yield and 0.46 gL-1.h-1 productivity for pitaya vinegar. The alcoholics fermented and físalis and pitaya acetic showed polyphenols and antioxidant capacity, and therefore sources of bioactive substances. The vinegar can be successfully produced from alcoholic fermented físalis and pitaya, using a mixed culture of A. aceti, the pasteurianus and G. oxydans.